Prototipe Sistem Keamanan Parkir berbasis Teknologi RFID - Sasmita Eko Raharjo; Agung Setia Budi; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Parking is a process for every vehicle that stops at a certain place. Parking areas owned by agencies, institutions, and institutions should prioritize service and security for the sake of parking eligibility. The parking system that has been implemented so far is still being implemented with limited number of human guards, so it has many loopholes for theft to occur without the vehicle owner knowing. RFID technology is a solution for today in solving the problem of theft and contactless technology. Several studies have been conducted, many of which are used only as a parking area monitoring tool. The lack of a system/tool that is usually used to respond when a vehicle is lost belonging to a parking area user is a problem for both the parking area owner and the vehicle owner. This security system is made using RFID technology, Load-Cell sensors, and GSM modules as a solution to related problems. From the manufacture of the system, of course, it is necessary to test the problem of delay or response speed when a theft occurs. The results of the tests and analyzes carried out get pretty good numbers, namely around 2 seconds to provide notification in the form of SMS to vehicle owners, and about 5 seconds for the system to close the portal when it is open. The response given is the result of data transactions from the sensor node to the Gatekeeper node using the ESP-NOW protocol communication. The Gatekeeper node is also used to communicate with the basis data, in terms of verifying whether the user is registered or not. Registered user data will of course be recorded when accessing the parking area when entering or exiting and displayed on a web page.